Compound-complex sentences functioning in the minimal text units (dictemas) - Prokhorova, Olga N.; Chekulai, Igor V.; Mironova, Galina V.; Pupynina, Elena V.; Poymenova, Alisa S. (Universidade Estadual Paulista, 2021)
The article studies the compound-complex sentences functioning in the minimal text units – dictemas. The authors analyze the location of minimal constructions of a compound-complex sentence within a dictema and they conclude that the most typical position is the middle of the dictema. The study shows that the minimal constructions of the compound-complex sentence can be both optional and meaning-forming components of a minimal text unit. The minimal constructions of the compound-complex sentence are polyfunctional.  They realize intra-dictemic and inter-dictemic functions, as well as the text-forming function in the text.